VD_FINDINFO Jug / 2014 / 238 vom 20. März 2014 - VD Tribunal cantonal (2014)
VOIES DE FAIT, DROIT DE CORRECTION, ÉDUCATION, CONSTATATION DES FAITS, DÉPENS | 126 al. 1 CP, 126 al. 2 CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH), 433 al. 1 CPP(CH)